2014
DOI: 10.1136/medethics-2013-101765
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a consent for chart review and contact and its impact in one clinical centre

Abstract: Consent for chart review and contact addresses several important ethical issues regarding the use of patient clinical information for research purposes. Our study demonstrated how such a process can be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Several studies have documented the implementation of registries which utilise this recruitment method [ 23 26 ]. Studies have demonstrated it to be cost efficient [ 24 , 25 ], accelerate patient involvement in research [ 23 , 24 ], have high consent rates [ 23 , 25 , 26 ] and to improve consumer autonomy by reducing the role of the clinician as a ‘gatekeeper’ [ 23 ]. With this method demonstrating such promising results, there is an urgent need to continue this research through the consideration of consumer preferences for research participation, such as frequency of participation and methods of contact.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented the implementation of registries which utilise this recruitment method [ 23 26 ]. Studies have demonstrated it to be cost efficient [ 24 , 25 ], accelerate patient involvement in research [ 23 , 24 ], have high consent rates [ 23 , 25 , 26 ] and to improve consumer autonomy by reducing the role of the clinician as a ‘gatekeeper’ [ 23 ]. With this method demonstrating such promising results, there is an urgent need to continue this research through the consideration of consumer preferences for research participation, such as frequency of participation and methods of contact.…”
Section: Introductionmentioning
confidence: 99%
“…32 Others have suggested that while uptake to specific research may increase among those giving permission to contact (compared to those recruited through traditional physician-mediated contacts), there may be significant differences in the age and gender of those who agreed compared to those who declined the permission to contact form. 33 A further consideration is whether a permission to contact agreement constitutes a valid consent. Studies indicate that there may be confusion among patients as to whether they were immediately signing up to research, 34 and this may be especially true when patients are recruited upon arrival to the hospital prior to diagnosis.…”
Section: Countervailing Trendsmentioning
confidence: 99%
“…There are several models for sign-up, including allowing patients to sign up on their own at home, on their own in the clinic at a kiosk, or with help from staff at a clinic appointment. Available data suggest that patient registries are cost-effective [13,14], increase patient involvement in research [12,14] have high consent rates [13,19], and improve patient autonomy [12]. For example, data from Rimel et al suggest that online registries can boost participation by more than 4 times compared with paper registries, with higher participation from minorities [20].…”
Section: Journal Of Clinical and Translational Sciencementioning
confidence: 99%